Individual’s Psychological State and Family - Purvaneckienė, Giedrė (Acta Paedagogica Vilnensia, 1993)
The article is based on a paper presented in the European Congress on Mental Health in European Families (Prague, May 1991). It draws on results of the values survey conducted in 1990. In this survey 1,000 respondents were interviewed using a representative national sample. Factor and cluster analysis broke down respondents into two groups – those who have recently felt more positive than negative emotions, and those who have recently felt more negative than positive emotions – and revealed that they correspond to the characteristics of the family. The first group contained more men, married people, the second – women and widows. This survey also confirmed attitudes to the family and the relationships within it that were revealed by previous surveys. A three-dimensional model is used to describe them. Cultural harmony, the factors supporting the relationship (relationship supporting resources) and interpersonal harmony were distinguished. Generally it can be said that all the factors of this model have an impact on an individual’s psychological well-being.